Fundamental Dilemmas Concerning the Constitutional Arrangements for the Formation of the Government in the Republic of Slovenia - Rudi Kocjančič (Central European Public Administration Review)
In Slovenia, even twenty years after the adoption of its Constitution, the amendments to the constitutional arrangements for the appointment of ministers represent one of the fundamental constitutional dilemmas of the political elite and experts on constitutional law. The following two variants are most topical: according to the first variant, following the example of the German constitution, ministers would be appointed by the president of the republic on the proposal of the president of the government, elected by the National Assembly; according to the second variant, the National Assembly would elect the president of the government together with the submitted candidate list of ministers. Nevertheless, the appointment of ministers according to the chancellorship model, which excludes the parliament from any voting on their appointment, i.e. also from the vote of investiture on the government, would undermine their legitimacy and disproportionally strengthen the constitutional position of the president of the government. In contrast, the election of the president of the government together with candidates for ministers would be significantly more transparent and legitimate. However, it will not be possible to form a stable government without changing the electoral system, which systemically causes party fragmentation of the National Assembly.